Preparation method and application of iron-doped basic cobalt silicate electrocatalyst

By synthesizing iron-doped alkaline cobalt silicate electrocatalysts with natural Elosite as the silicon source, the existing alkaline cobalt silicate electrocatalysts have been solved, and high efficiency and low stability are achieved Cost electrocatalytic performance improvement.

CN119162607AActive Publication Date: 2024-12-20HEBEI UNIV OF TECH

Patent Information

Application Number
CN202411357480.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-20
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing alkaline cobalt silicate electrocatalysts have low oxygen evolution efficiency, high synthesis cost and poor stability, especially when using traditional silicon sources such as Na2SiO3·9H2O or SiO2, it is difficult to control the reaction process, resulting in uneven extension of the nanostructure.

Method used

Using natural tubular elerosite as the silicon source, high-purity SiOx nanotubes were obtained through calcination activation and purification, and iron-doped basic cobalt silicate (CoFeSi) electrocatalyst was synthesized through hydrothermal reaction, and the catalysis was improved by iron doping. active.

Benefits of technology

It realizes an electrocatalyst with low cost, simple synthesis, high oxygen evolution efficiency and excellent stability. The overpotential decreases and the Tafel slope decreases. The catalyst exhibits faster reaction kinetics at lower overpotentials and has a good long-term stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162607A_ABST
    Figure CN119162607A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of an iron-doped basic cobalt silicate electrocatalyst. The method comprises the following steps: (1) placing natural halloysite powder in a muffle furnace, dispersing calcined halloysite in hydrochloric acid, and stirring to obtain a first suspension; (2) transferring the first turbid liquid into a reaction kettle, sealing, and reacting at 100-140 DEG C for 10-14 hours to obtain a silicon oxide (SiOx) nanotube; and (3) adding the SiOx nanotube, cobalt nitrate hexahydrate and ferric nitrate nonahydrate into a mixed solvent, stirring, dropwise adding ammonia water, then adding NH4Cl, continuously stirring for 20-40 minutes, transferring the obtained turbid liquid into a reaction kettle, sealing, and reacting at 130-170 DEG C for 12-20 hours to obtain the CoFeSi electrocatalyst. The CoFeSi electrocatalyst synthesized by the method has the characteristics of low cost, simplicity in synthesis, high oxygen evolution efficiency, excellent stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic electrocatalytic materials, and specifically relates to a preparation method and application of an iron-doped basic cobalt silicate electrocatalyst. Background Art

[0002] Basic cobalt silicate (CoSi) is a new type of oxygen evolution reaction (OER) electrocatalyst. Its structure is similar to the layered structure of hydroxyl oxide, but its synthesis cost is lower than that of hydroxyl oxide, and there are abundant hydroxyl groups and metal active sites on the surface. Its special structure and unique electron transfer pathway make it one of the most promising OER catalysts. At present, the silicon source required for the synthesis of CoSi generally comes from industrially synthesized Na2SiO3·9H2O and SiO2 synthesized by different methods. However, when synthesizing CoSi using traditional silicon sources such as Na2SiO3·9H2O or SiO2 as raw materials, it is difficult to control the reaction process and the nanostructure cannot be uniformly extended in an alkaline environment, so it is difficult to achieve controllable preparation. Materials with high silicon content and special structure can not only be used as the silicon source required for the controllable synthesis of CoSi, but also as templates to grow nanoscale CoSi on their surface. Based on this, silicon oxides (SiO x ) began to attract attention.

[0003] At the same time, the electrocatalytic activity of CoSi still needs to be further improved. For a given catalyst structure framework, introducing cations by chemical methods to achieve cation diversity is one of the simple ways to improve the electrocatalytic performance. This is because different metals in the catalyst will interact with each other, further affecting the electronic structure, causing strain in the original geometry, so that the energy of the intermediates involved in the OER process is optimized. For example, Chinese patent CN 115386908 A discloses a method for preparing an iron-cobalt-nickel double hydroxide (LDH) nanocage electrocatalytic oxygen evolution material. The catalytic activity of the Fe-Co-Ni LDH-based electrocatalyst is further improved based on the strong coupling synergistic effect of the active sites of the three metals of Fe, Co and Ni, but its preparation cost is still higher than that of the basic cobalt silicate-based electrocatalyst prepared with silicate minerals as silicon source; Chinese patent CN 118326451 A prepares a nickel-doped cobalt MOF-74 electrocatalytic oxygen evolution material. The nickel doping adjusts the electronic structure of the material and improves the catalytic activity, but toxic reagents such as methanol are required in the preparation process. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an iron-doped basic cobalt silicate electrocatalyst to solve the problems of low oxygen evolution efficiency, high synthesis cost and poor stability of current electrocatalysts. The method uses natural tubular halloysite as a silicon source, and obtains SiO2 with high purity after calcination, activation and purification.x Nanotubes are then used as raw materials to synthesize iron-doped basic cobalt silicate (CoFeSi) electrocatalysts through simple hydrothermal reactions. The CoFeSi electrocatalyst synthesized by the invention has the characteristics of low cost, simple synthesis, high oxygen evolution efficiency and excellent stability.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] A method for preparing an iron-doped basic cobalt silicate electrocatalyst, the method comprising the following steps:

[0007] (1) placing natural halloysite powder in a muffle furnace and calcining at 700-750° C. for 2-4 hours; dispersing the calcined halloysite in hydrochloric acid and stirring to obtain a first suspension;

[0008] Wherein, 1 to 2 g of the calcined product of natural halloysite powder is added to every 60 mL of hydrochloric acid; the concentration of the hydrochloric acid is 1 to 2 mol / L;

[0009] (2) The first suspension is transferred to a reaction kettle, sealed and reacted at 100-140°C for 10-14 hours, and then washed and dried to obtain silicon oxide (SiO x ) nanotubes, spare;

[0010] (3) Silicon oxide (SiO x ) nanotubes, cobalt nitrate hexahydrate and ferric nitrate nonahydrate are added to the mixed solvent, and stirred to obtain a second suspension;

[0011] Wherein, 0.02-0.04 g SiO is added to every 10-12 mL of mixed solvent. x Nanotubes, 0.2-0.5 g of Co(NO3)2·6H2O, 0.1-0.3 g of Fe(NO3)3·9H2O; the mixed solvent is composed of ethanol and deionized water, and the volume ratio of ethanol to deionized water is 4:1-2:1;

[0012] (4) adding ammonia water to the second suspension, and then adding NH4Cl and stirring continuously for 20 to 40 minutes, transferring the obtained suspension into a reaction kettle, sealing it, reacting it at 130 to 170° C. for 12 to 20 hours, washing and drying it after the reaction, and obtaining a CoFeSi electrocatalyst;

[0013] Wherein, 2-4 mL of ammonia water and 0.4-0.6 g of NH4Cl are added to every 10-12 mL of the second suspension; the concentration of the ammonia water is 1.0-1.5 mol / L;

[0014] The iron-doped basic cobalt silicate electrocatalyst prepared by the method is used for oxygen evolution reaction by electrolysis of water.

[0015] Specifically, the three-electrode system performs constant current electrolysis on the KOH solution, a hydrogen evolution reaction (HER) occurs at the cathode to obtain hydrogen, and an oxygen evolution reaction (OER) occurs at the anode to obtain oxygen;

[0016] The electrocatalyst contains iron-doped basic cobalt silicate as the working electrode (anode), Hg / HgO as the reference electrode, and a carbon rod as the counter electrode (cathode); the current density is 5 to 20 mA cm -2 ;

[0017] The concentration of KOH solution is 0.5~2M;

[0018] The preparation method of the working electrode comprises: adding an iron-doped basic cobalt silicate electrocatalyst into a mixed solution to obtain a suspension, then coating the suspension on a carbon cloth, and drying the suspension to obtain a working electrode;

[0019] Wherein, 1 to 10 mg of catalyst is added to every 500 μL of mixed solution; and 20 to 100 μL of suspension is coated on every square centimeter of carbon cloth.

[0020] The composition of the mixed solution is water, Nafion and isopropanol, and the volume ratio of the three is 14:35:1.

[0021] The raw materials, reagents and equipment involved in the preparation method of the iron-doped basic cobalt silicate electrocatalyst are all obtained through well-known routes, and the operation process can be mastered by those skilled in the art.

[0022] The essential features of the present invention are:

[0023] Iron-doped basic cobalt silicate nanosheets were successfully synthesized using natural clay mineral halloysite as silicon source and template. The basic cobalt silicate was modified by iron doping. The synthesized CoFeSi had no impurities and exposed more vacancy defects due to the low degree of crystallization, which can improve the corresponding catalytic efficiency. The hollow structure formed by the assembly of CoFeSi nanosheets on the surface of one-dimensional halloysite nanotubes greatly exposed the reaction active sites. The specific surface area of ​​CoFeSi is much larger than that of CoSi. The larger specific surface area is conducive to more catalytic active sites participating in the catalytic reaction. The larger pore size distribution and the bimetallic synergistic effect produced by Fe element doping significantly improved the OER performance of the material.

[0024] The beneficial effects of the present invention are:

[0025] (1) Using the natural clay mineral halloysite as the silicon source instead of industrial raw materials such as sodium silicate or ethyl orthosilicate to prepare CoFeSi nanosheets can effectively reduce the preparation cost, and the tubular structure of halloysite can provide a template for the growth of CoFeSi nanosheets.

[0026] (2) Fe doping causes the binding energy of Co 2p to shift to a lower position, and the bimetallic synergistic effect produced by doping greatly improves the OER reaction performance of the catalyst.

[0027] (3) The present invention utilizes a hydrothermal method to prepare CoFeSi nanosheet electrocatalysts, and the preparation process is relatively simple and has a high tolerance to experimental parameters.

[0028] (4) The CoFeSi electrocatalyst disclosed in the present application has a current density of 10 mA cm -2 The overpotential is only 282 mV, which is much lower than commercial RuO2 (321 mV) and CoSi in the comparative example (347 mV), and the Tafel slope is only 57 mV·dec -1 , which is also much lower than commercial RuO2 (71mV·dec -1 ) and the CoSi in the comparative example (97mV·dec -1 ), has an earlier onset potential and faster reaction kinetics, and has good long-term stability.

[0029] (5) The silicon source used in the synthesis of the CoFeSi electrocatalyst disclosed in this application is not limited to halloysite. This research result provides an important reference for the subsequent research and preparation of natural clay mineral-based OER catalysts.

[0030] The present invention provides a preparation method and application of an iron-doped basic cobalt silicate electrocatalyst, which uses natural tubular halloysite as a silicon source, undergoes calcination, activation and purification treatment, and first obtains SiO x The nanotubes were then used as raw materials to synthesize iron-doped cobalt basic silicate electrocatalyst (CoFeSi) through a simple hydrothermal reaction. The catalytic activity of the electrocatalyst was significantly improved compared with that of CoSi, with the overpotential reduced from 347mV to 282mV and the Tafel slope reduced from 97mV·dec -1 Reduced to 57mV·dec -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 XRD patterns of CoSi prepared in Comparative Example 1 and CoFeSi with different iron addition amounts prepared in Examples 1-3.

[0032] Figure 2 FT-IR graphs of CoSi prepared in Comparative Example 1 and CoFeSi with different iron addition amounts prepared in Examples 1-3.

[0033] Figure 3 The SEM images of CoSi prepared in Comparative Example 1 and CoFeSi with different iron addition amounts prepared in Examples 1-3 are shown; wherein, Figure 3(a) is the SEM image of CoSi. Figure 3 (b) is the SEM image of 5wt.% iron doping, Figure 3 (c) is the SEM image of 10wt.% iron doping, Figure 3 (d) is the SEM image of 15 wt.% iron doping.

[0034] Figure 4 The BET analysis diagram of CoFeSi prepared in Example 1 and CoSi prepared in Comparative Example 1; wherein, Figure 4 (a) is the N2 adsorption-desorption isotherm of CoFeSi and CoSi. Figure 4 (b) is the pore size distribution curve of CoFeSi and CoSi.

[0035] Figure 5 The electrochemical performance curves of CoFeSi with different iron addition amounts prepared in Examples 1-3, wherein: Figure 5 (a) is the LSV curve, Figure 5 (b) is the Tafel slope diagram, Figure 5 (c) is C dl picture, Figure 5 (d) is the Nyquist diagram.

[0036] Figure 6 The stability test results of the CoFeSi electrocatalyst prepared in Example 1; wherein, Figure 6 (a) is the LSV polarization curve of CoFeSi before and after 3000 CV cycles. Figure 6 (b) CoFeSi at 10 mA·cm -2 Chronopotentiometry test results. DETAILED DESCRIPTION

[0037] The present invention will be described below with reference to specific embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0038] Example 1

[0039] Weigh 2 g of natural halloysite powder into a crucible and transfer it to a muffle furnace and calcine it at 730 °C for 3 h. Disperse the calcined halloysite in 60 mL of 2 mol / L hydrochloric acid solution, stir for 30 min, transfer it to a reactor, seal it and react at 120 °C for 12 h, then wash and dry it to obtain SiO x Nanotubes; weigh 0.03g SiO xNanotubes, 0.3g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 0.2g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O) were added to a mixture of 8mL of ethanol and 2mL of deionized water, stirred, and 3mL of 1.5mol / L ammonia water was added dropwise to the suspension, followed by adding 0.53g of NH4Cl and stirring continuously for 30min. The resulting suspension was transferred to a reactor, sealed and reacted at 150°C for 16h. After the reaction, it was washed and dried to obtain a CoFeSi electrocatalyst.

[0040] Example 2

[0041] The other steps are the same as those in Example 1, except that “2 g of halloysite” is replaced by “1 g of halloysite”, “2 mol / L of hydrochloric acid solution” is replaced by “1 mol / L of hydrochloric acid solution”, “0.2 g of Fe(NO3)3·9H2O” is replaced by “0.1 g of Fe(NO3)3·9H2O”, “2 mL of deionized water” is replaced by “4 mL of deionized water”, “3 mL of 1.2 mol / L of ammonia water” is replaced by “4 mL of 1.0 mol / L of ammonia water”, and “0.53 g of NH4Cl and continuous stirring for 30 min” is replaced by “0.4 g of NH4Cl and continuous stirring for 20 min”. The obtained CoFeSi electrocatalyst still exhibits good electrocatalytic activity.

[0042] Example 3

[0043] The other steps are the same as those in Example 2, except that “0.2 g Fe(NO3)3·9H2O” is replaced by “0.3 g Fe(NO3)3·9H2O”, “3 mL 1.2 mol / L ammonia water” is replaced by “2 mL 1.5 mol / L ammonia water”, and “0.53 g NH4Cl and continuous stirring for 30 min” is replaced by “0.6 g NH4Cl and continuous stirring for 40 min”. The obtained CoFeSi electrocatalyst still exhibits good electrocatalytic activity.

[0044] Comparative Example 1

[0045] The other steps are the same as those in Example 1, except that Fe(NO3)3·9H2O is not added during the preparation process, and the obtained CoSi nanosheets are washed and dried after the reaction for later use.

[0046] From the attached Figure 1 It can be seen that the characteristic peak positions of CoFeSi obtained with all Fe addition amounts are the same as those of CoSi, and Fe doping does not cause a shift in the diffraction peak position. With the change of Fe content, the intensity of the diffraction peak has almost no significant change, indicating that Fe doping does not affect the crystallinity of the catalyst.

[0047] From the attached Figure 2 It can be seen that the bonding characteristics of CoSi and CoFeSi functional groups are consistent with those of layered silicates. -1 The OH stretching vibration mode of OH-3M (M: Co / Fe) is 1009 cm, indicating the presence of top hydroxyl group (-OH) in MO6 in silicate. -1 and 460cm -1 The bending vibrations of Si-O and asymmetric Si-O are shown in Figure 3. The change in Fe addition did not lead to the appearance or disappearance of new functional groups. -1 and 1643cm -1 The absorption vibration peaks at correspond to the stretching vibrations of adsorbed water and surface OH functional groups on the sample surface, respectively.

[0048] From the attached Figure 3 From the SEM image of (a), we can see that the CoSi nanosheets self-assemble into a typical one-dimensional rod-like structure, and the thickness of the nanosheets is about 10nm. Figure 3 (b)- Figure 3 The SEM images of (d) show that the basic cobalt iron silicate nanosheets prepared under different Fe addition conditions are along the SiO x The nanotubes grow on the surface, and the nanosheets are thin and grow in an interlaced manner. As the Fe content increases, the nanosheets become thicker, but their length does not change significantly.

[0049] From the attached Figure 4 (a) shows the N2 adsorption-desorption isotherm. It can be seen that the adsorption-desorption curve of CoFeSi shows a classic type IV isotherm with an H3 type hysteresis loop, which proves the mesoporous characteristics of CoFeSi. More closely connected nanosheets make the S BET Reach 244m 2 / g, proving that the CoFeSi catalyst has more reactive sites than CoSi. Figure 4 From the pore size distribution curve (b), we can see that the average pore size of CoFeSi is 18 nm, which is much larger than that of CoSi. The larger pore size provides more diffusion possibilities.

[0050] Attached Figure 5 (a) shows the polarization curves of CoFeSi with three different Fe addition amounts and commercial RuO2. When the current density is 10 mA cm -2 When the overpotentials of CoFeSi-5 and CoFeSi-15 are 334 mV and 313 mV, respectively, the polarization of CoFeSi-10 occurs at a lower potential with the lowest overpotential, reaching 10 mA cm -2Only 282mV is needed. CoFeSi-10 has excellent OER activity, which is much higher than the commercial RuO2 electrocatalyst (overpotential is 321mV). Figure 5 (b) It can be seen that among the CoFeSi samples prepared under different Fe addition conditions, the Tafel slope of CoFeSi-5 is 62 mV·dec. -1 The Tafel slope of CoFeSi-15 is 66 mV·dec -1 , CoFeSi-10 has the smallest Tafel slope, only 57mV·dec -1 The lower Tafel slope indicates that CoFeSi-10 has a faster OER process, which enables the catalyst to obtain a relatively high catalytic current at a lower overpotential. Figure 5 (c) It can be seen that there is a linear relationship between Δj and the scanning speed. By calculating the slope, it is found that the double layer capacitance of CoFeSi-10 is 35.7 mF·cm -2 , compared with CoFeSi-5 (29.8mF·cm -2 ) and CoFeSi-15 (34.5mF·cm -2 ) has a higher double layer capacitance value due to the electrochemically active surface area and C dl There is a linear relationship between the active sites of CoFeSi-10 and the active sites of CoFeSi-10. Figure 5 (d) It can be seen that the Nyquist plot fits the dual time constant and equivalent circuit model well, and CoFeSi-10 exhibits the lowest R ct (4.05Ω), corresponding to a faster electron transfer rate. This is because the appropriate amount of Fe added leads to a favorable bimetallic synergistic effect between Fe and Co. Under this addition condition, the electron transfer between Fe and Co is more conducive to the OER reaction.

[0051] The oxygen evolution reaction performance of all electrocatalysts was tested using a three-electrode system. The electrocatalysts were drop-coated on carbon cloth as the working electrode, Hg / HgO was selected as the reference electrode, and carbon rods were used as the counter electrode. All electrochemical performance tests were performed at room temperature using 1M KOH solution. The conversion formula between Hg / HgO and RHE and the equation corresponding to the overpotential (η) are as follows:

[0052] E RHE =E Hg / HgO +0.059×pH+0.098

[0053] η=E RHE -1.23V

[0054] The preparation steps of the working electrode are as follows: take 5 mg of catalyst powder and add it to a mixture of water, Nafion and isopropanol (140 μL of water, 350 μL of isopropanol, and 10 μL of Nafion solution), sonicate until the mixture is uniform, then take 50 μL of the suspension and drop it on the cut carbon cloth (size is 1 cm×1 cm), and dry it naturally at room temperature for use.

[0055] The polarization curves were obtained by linear sweep voltammetry. The scan rate of the LSV test in this experiment was 5 mV·s -1 , iR compensation is 90%. The Tafel slope curve is a curve that conforms to the Tafel relationship, which is obtained by transforming the LSV curve according to the following formula:

[0056] η=alogj+b

[0057] Where η is the overpotential, j is the current density, and the values ​​of a and b are determined by the material itself.

[0058] The stability test of the catalyst is an important indicator for evaluating whether the catalyst can maintain stable performance for a long time and whether it can be applied. The current test methods for the stability of the catalyst in the classic three-electrode system include cyclic voltammetry and chronopotentiometry (CP). This work measured the stability of the catalyst by continuous 3000 cyclic voltammetry tests at a constant current density of 10mA·cm -2 Under the conditions, 10 5 The long-term stability of the catalyst was further evaluated by chronopotentiometry curves.

[0059] From the attached Figure 6 (a) It can be seen that the stability of CoFeSi was tested by continuous 3000 CV tests. From the polarization curve of CoFeSi, it can be seen that the performance of CoFeSi was improved after 3000 CV cycles, which may be caused by the exposure of more metal active sites during the test. Chronopotentiometry (CP) is also an important parameter for measuring catalyst stability. At j = 10 mA cm -2 Under constant conditions, the stability of CoFeSi was analyzed by chronopotentiometry. Figure 6 (b) It can be seen that CoFeSi at 10 5 The potential did not change significantly within s, indicating that there was no structural degradation on the CoFeSi surface during the test. The results show that the electrocatalyst maintained excellent durability and stability throughout the test.

[0060] It can be seen from the above embodiments and comparative examples that the present invention successfully synthesized basic cobalt silicate using the natural clay mineral halloysite as a silicon source and template by a hydrothermal method, and further improved the oxygen evolution reaction performance of the basic cobalt silicate nanosheets by the bimetallic synergistic effect produced by iron doping.

[0061] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

[0062] Matters not covered by the present invention are known technologies.

Claims

1. A method for preparing an iron-doped basic cobalt silicate electrocatalyst, characterized in that the method comprises the following steps: (1) placing natural halloysite powder in a muffle furnace and calcining at 700-750° C. for 2-4 hours; dispersing the calcined halloysite in hydrochloric acid and stirring to obtain a first suspension; Wherein, 1 to 2 g of the calcined natural halloysite powder is added to every 60 mL of hydrochloric acid; (2) transferring the first suspension into a reaction kettle, sealing it, reacting it at 100-140° C. for 10-14 hours, and then washing and drying it to obtain silicon oxide nanotubes; (3) adding silicon oxide nanotubes, cobalt nitrate hexahydrate and ferric nitrate nonahydrate into a mixed solvent, and stirring to obtain a second suspension; Wherein, 0.02-0.04 g of silicon oxide nanotubes, 0.2-0.5 g of Co(NO3)2·6H2O, and 0.1-0.3 g of Fe(NO3)3·9H2O are added to every 10-12 mL of the mixed solvent; the mixed solvent is composed of ethanol and deionized water, and the volume ratio of ethanol to deionized water is 4:1-2:1; (4) adding ammonia water to the second suspension, and then adding NH4Cl and stirring continuously for 20 to 40 minutes, transferring the obtained suspension into a reaction kettle, sealing it, reacting it at 130 to 170° C. for 12 to 20 hours, washing and drying it after the reaction, and obtaining a CoFeSi electrocatalyst; Wherein, 2-4 mL of ammonia water and 0.4-0.6 g of NH4Cl are added to every 10-12 mL of the second suspension.

2. The method for preparing the iron-doped basic cobalt silicate electrocatalyst according to claim 1, characterized in that In step (1), the concentration of hydrochloric acid is 1-2 mol / L.

3. The method for preparing the iron-doped basic cobalt silicate electrocatalyst according to claim 1, characterized in that In step (4), the concentration of aqueous ammonia is 1.0 to 1.5 mol / L.

4. The use of the iron-doped basic cobalt silicate electrocatalyst prepared by the method according to claim 1, characterized in that it is used for oxygen evolution reaction by electrolysis of water.

5. The use according to claim 4, characterized in that the three-electrode system performs constant current electrolysis on the KOH solution, a hydrogen evolution reaction (HER) occurs at the cathode to obtain hydrogen, and an oxygen evolution reaction (OER) occurs at the anode to obtain oxygen; in, The electrocatalyst contains iron-doped basic cobalt silicate as the working electrode (anode), Hg / HgO as the reference electrode, and a carbon rod as the counter electrode (cathode); the current density is 5-20 mA cm -2 ; The concentration of KOH solution is 0.5~2M.

6. The use according to claim 5, characterized in that the preparation method of the working electrode is: adding the iron-doped basic cobalt silicate electrocatalyst to the mixed solution to obtain a suspension, then coating the suspension on a carbon cloth, and drying to obtain the working electrode; in, 1-10 mg of catalyst is added to every 500 μL of mixed solution; 20-100 μL of suspension is coated on every square centimeter of carbon cloth.

Citation Information

Patent Citations

  • Bifunctional oxygen electrocatalyst taking hollow carbon nanotube as carrier, preparation and application

    CN112886029A

Cited By

  • Electrode material based on rare earth doping and preparation method thereof

    CN121076159A